Meningkatkan Partisipasi Siswa Melalui Metode Project Based Learning dalam Pendidikan Agama Islam - Caren Patrysha; Nurul Azizah; Gusmaneli Gusmaneli (Badan Penerbit STIEPARI Press, 2024)
Project Based Learning is a learning model that uses projects or activities as media. In project-based learning, students are involved in real projects that are relevant to Islamic learning material. This increases students' interest and motivation in learning, and allows them to apply Islamic religious knowledge in everyday life. Project-based learning can improve students' social skills, such as cooperation in groups, communication, and problem solving. The teacher as a facilitator gives tasks to students to develop their potential. Several stages in PAI learning using a project-based learning model are as follows. Apart from that, students also develop a deeper understanding of Islamic religious values through direct experience in the projects they work on.